Sensory, Microbiological and Chemical Assessment of Cod (Gadus morhua) Fillets during Chilled Storage as Influenced by Bleeding Methods - Minh Van Nguyen; Magnea Gudrun Karlsdottir; Adalheidur Olafsdottir; Arnljotur Bjarki Bergsson; Sigurjon Arason (Zenodo, 2013)
The effects of seawater and slurry ice bleedingmethods on the sensory, microbiological and chemical qualitychanges of cod fillets during chilled storage were examined in thisstudy. The results from sensory evaluation showed that slurry icebleeding method prolonged the shelf life of cod fillets up to 13-14days compared to 10-11 days for fish bled in seawater. Slurry icebleeding method also led to a slower microbial growth andbiochemical developments, resulting lower total plate count (TPC),H2S-producing bacteria count, total volatile basic nitrogen (TVB-N),trimethylamine (TMA), free fatty acid (FFA) content and higherphospholipid content (PL) compared to those of samples bled inseawater. The results of principle component analysis revealed thatTPC, H2S-producing bacteria, TVB-N, TMA and FFA were insignificant correlation. They were also in negative correlation withsensory evaluation (Torry score), PL and water holding capacity(WHC).